2017
DOI: 10.1002/phar.1928
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ABCC2, CYP2C8, and CYP2J2 Polymorphisms on Tacrolimus and Mycophenolate Sodium–Based Treatment in Brazilian Kidney Transplant Recipients

Abstract: The ABCC2 c.3972C >T polymorphism affected tacrolimus C:D in Brazilian kidney transplant recipients. Further, CYP2C8*3 and CYP2J2 c.-76G>T SNPs influenced the renal function of these patients and the occurrence of adverse events during treatment with tacrolimus and mycophenolate sodium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…The CC genotype of another SNP (rs2280275) has been suggested to be a genetic marker for risk of essential hypertension in an Uygur population but not in a Han population [ 112 ]. The CYP2J2*7 SNP has also been reported to affect the renal function and the risk of adverse events associated with tacrolimus and mycophenolate sodium in kidney transplant patients in Brazil [ 113 ]. Although not conclusive, CYP2J2 genetic variation may reduce EET levels, which could potentially lead to hypertension.…”
Section: Protective Role Of Cyp2j2 In the Kidneymentioning
confidence: 99%
“…The CC genotype of another SNP (rs2280275) has been suggested to be a genetic marker for risk of essential hypertension in an Uygur population but not in a Han population [ 112 ]. The CYP2J2*7 SNP has also been reported to affect the renal function and the risk of adverse events associated with tacrolimus and mycophenolate sodium in kidney transplant patients in Brazil [ 113 ]. Although not conclusive, CYP2J2 genetic variation may reduce EET levels, which could potentially lead to hypertension.…”
Section: Protective Role Of Cyp2j2 In the Kidneymentioning
confidence: 99%
“…On the other hand, many genetic polymorphisms within Phase II drug metabolizing genes were defined as VIP variants and related to different diseases important to pharmacogenetics. Within UGT1A1 gene the rs8175347 and rs10929302 (AA) have been implicated in toxicity, increased risk of diarrhea and neutropenia when treated with irinotecan in people with colorectal neoplasms [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Capron et al . found that patients with the ABCB1 3435T or the 2677T/A allele had 1.3-fold higher Tac concentrations within circulating lymphocytes compared with wild-type homozygotes [ 107 ]. These studies provide evidences that ABCB1 3435C>T and 2677G>T/A affect Tac distribution into lymphocytes with the variant alleles which are associated with an increased pharmacodynamic effect of Tac.…”
Section: Pharmacogeneticsmentioning
confidence: 99%